Pemberdayaan tenaga kesehatan pada fasilitas kesehatan primer di Kecamatan Sungsang: pengenalan kanker kulit - Yahya, Yulia Farida; Toruan, Theresia L; Kurniawati, Yuli; Nopriyati, Nopriyati; Argentina, Fifa; Trilisnawati, Damai; Findrapase, Riri Puspa Putri; Deddy, Deddy; Antonius, Cayadi Sidarta; Saputra, M. Akip Riyan; Fantoni, Odelia Jovita Jusuf; Candra, Nofilia Citra (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Empowering health workers at primary health facilities in Marga Sungsang Village: introduction to skin cancer. Skin cancer is a skin malignant tumor derived from keratinocytes and melanocyte cells, known as keratinocyte carcinoma and cutaneous melanoma, the most common is keratinocyte carcinoma consisting of Basal cell carcinoma(BCC) and Squamous cell carcinoma (SCC) and rarely cutaneous melanoma (MM). The incidence has increased sharply around the world, especially in Palembang. The study in Palembang at RSMH (2017-2019) found that there was an increase of skin cancer is five times compared to previous studies. Generally, skin cancer patients referred to tertiary hospitals are in the advanced stage and accompanied by complications, increasing morbidity and mortality, making therapy difficult. so the cost of hospital care is high and becomes a burden to the state. The problem for health workers in primary health facilities is that knowledge about skin cancer is still low and this knowledge is only obtained during education level. The purpose is to improve and develop the knowledge of primary health care workers by Oncologist and skin surgeon and lecturer in Dermatology and Venereology FK Unsri / RSMH Palembang, about skin cancer and its problems, reducing the incidence and finding new cases of skin cancer, preventing skin cancer an advanced stage in primary health facilities. The counseling in the village of Marga Sungsang, Sungsang sub-district, 27 participants consist of 26 women (96,3%) and 1 male (3,7%) participants, with varied in age, the youngest was 18 years and highest was 44 years old. Education level: SMA as 20 participants (74.0%) and S1 / AMK level as 7 participants (25.9%). The results of the pretest and posttest knowledge showed a 5-fold increase posttest compared to the pretest. The knowledge of skin cancer health workers is still low. Counseling is needed for all health workers and community leaders in the Banyuasin district.